The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41477-021-00989-9
|View full text |Cite
|
Sign up to set email alerts
|

A non-duplicated magnoliid genome

Abstract: Almost all flowering plants bear traces of ancient polyploidy. Now, the genome of a magnoliid, Aristolochia fimbriata, is described that is showing no evidence of whole genome duplication (WGD), a feature uniquely shared with Amborella trichopoda, the sister species to all other angiosperms. Since diploidization following polyploidy usually leads to major rearrangements of the genome, the more conserved, ancestral structure of the Aristolochia genome offers great opportunities for comparative genomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The clade of magnoliids comprises approximately 9000 species, accounting for approximately 3% of the species in angiosperms and includes many economically important species as sources of fruits, medicine, spices, and perfumes. The classification and phylogenetic position of magnoliids in mesangiosperms has been a long-lasting debate (Li et al, 2019;Li & Van de Peer, 2021;One Thousand Plant Transcriptomes, 2019). Mesangiosperms include five lineages, namely monocots, eudicots, magnoliids, Chloranthales, and Ceratophyllales (APG IV, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The clade of magnoliids comprises approximately 9000 species, accounting for approximately 3% of the species in angiosperms and includes many economically important species as sources of fruits, medicine, spices, and perfumes. The classification and phylogenetic position of magnoliids in mesangiosperms has been a long-lasting debate (Li et al, 2019;Li & Van de Peer, 2021;One Thousand Plant Transcriptomes, 2019). Mesangiosperms include five lineages, namely monocots, eudicots, magnoliids, Chloranthales, and Ceratophyllales (APG IV, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, until recently, only A. trichopoda (Albert et al, 2013), the sister species to all angiosperms, showed no evidence of WGD. Therefore, the recent availability of genome sequences of A. fimbriata , A. contorta , and also A. cherimola could facilitate future comparative genomics and evolution history studies of other species (Li & Van de Peer, 2021; Qin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A. cherimola could facilitate future comparative genomics and evolution history studies of other species (Li & Van de Peer, 2021;Qin et al, 2021).…”
Section: Comparative Genomicsmentioning
confidence: 99%